2019
DOI: 10.1016/j.fuel.2019.04.164
|View full text |Cite
|
Sign up to set email alerts
|

Underground coal gasification – A numerical approach to study the formation of syngas and its reactive transport in the surrounding strata

Abstract: In this work, a method to study the formation of syngas during the underground coal gasification (UCG) process and its reactive transport in the surrounding strata is proposed. It combines a thermodynamic equilibrium stoichiometric model of the cavity reactions with a coupled thermo-hydraulic-chemical-mechanical (THCM) framework of COMPASS code for the transport of UCG products away from the cavity. With the input information of coal properties obtained from the South Wales coalfield, gasification reagents (ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…During UCG, coal deposits are transformed into gaseous combustible products (syngas) and extracted to the surface. The quality of the product gas depends, to a large extent, on the gasification medium used, operating conditions, coal rank, and local hydrogeology [5][6][7][8][9][10]. UCG can be a viable extraction technology for coal seams, for which conventional coal mining technologies are technically, economically, or environmentally not feasible [11].…”
Section: Introductionmentioning
confidence: 99%
“…During UCG, coal deposits are transformed into gaseous combustible products (syngas) and extracted to the surface. The quality of the product gas depends, to a large extent, on the gasification medium used, operating conditions, coal rank, and local hydrogeology [5][6][7][8][9][10]. UCG can be a viable extraction technology for coal seams, for which conventional coal mining technologies are technically, economically, or environmentally not feasible [11].…”
Section: Introductionmentioning
confidence: 99%
“…The final product gas consists mainly of hydrogen, carbon monoxide, carbon dioxide, methane and nitrogen. Composition and calorific value of the product gas depend largely on the gasifying agent employed, thermodynamic conditions of the operation, coal rank and local hydrogeological conditions [16][17][18][19][20]. Several examples exist in literature demonstrating that under appropriate control of the process, the UCG could be oriented on the production of a specific product, such as hydrogen [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, research findings have highlighted the operational similarity between UCG and surface fixed-bed gasifiers with regard to synthesis gas composition [34][35][36]. Numerous previous studies focussing on UCG operation and optimization have used the equilibrium modeling approach [26,[37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…These models have been published using different classifications, designations and categories [13]. Gasification simulation models can be generally classified into the following three groups: thermodynamic equilibrium [14,15,17,18,[22][23][24][25][26], kinetic [27][28][29][30] and artificial neural network (ANN) models [31,32]. Guo et al [31] have shown that ANNs, which have been extensively used in the fields of pattern recognition, signal processing, function approximation and process simulation can also be applied to predict product yield and synthesis gas compositions of a gasification process.…”
mentioning
confidence: 99%